Review of Vanadium Production Part I: Primary Resources. (19th May 2022) - Gao, Feng; Olayiwola, Afolabi Uthmon; Liu, Biao; Wang, Shaona; Du, Hao; Li, Jianzhong; Wang, Xindong; Chen, Donghui; Zhang, Yi
ABSTRACT: Vanadium is a strategic transition metal that has been extensively utilized in steelmaking, green chemistry, energy storage, and aviation industries, and the sustainable development of vanadium production industries is therefore of significant importance. In this review, the production of vanadium using primary resources including vanadium titano-magnetite, vanadium slag, vanadium bearing stone coal, and carnotite has been reviewed, with the elaboration of typical industrial processes. The processes with respect to the cleaner production of vanadium have been discussed in detail to provide information for peer researchers to understand the challenges of this industry and future research directions. In addition, the resource, market, and major organizations of vanadium production have also been discussed in this review, presenting a general overview of this important industry.